Rasionalitas Tauhid dalam Dialog Nabi Ibrahim as dan Raja Namrud: Kajian Tafsir QS. Al-Baqarah Ayat 258 - St Magfirah (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2026)
This article discusses the conversation between Prophet Ibrahim as and King Namrud recounted in Surah Al-Baqarah, verse 258. The conversation depicts a discussion regarding the attributes of Allah and His power. This verse reflects the wisdom of Prophet Ibrahim as in delivering his message, which did not rely on empty rhetoric or coercion, but rather on a simple yet logical, argumentative and effective approach to refute King Namrud’s claims to divinity. This study explains the meaning of the verse using an interdisciplinary approach through a review of classical and modern exegetical literature (exegetical works such as Jami' al-Bayan fi Ta'wil al-Qur'an by al-Thabari, Tafsir al-Qur'an al-‘Azhim by Ibn Katsir, Al-Jami’ li Ahkam al-Qur'an by al-Qurthubi and Tafsir al-Misbah by M. Quraish Shihab). This study employs the tahlili method combined with historical, philosophical and sociological approaches. The research findings indicate that this discussion not only holds theological value but also conveys moral and social messages in confronting oppressive power. Prophet Ibrahim’s arguments demonstrate the power of reason in conveying the doctrine of tawhid without resorting to violence and serve as a model for conveying the truth wisely and firmly. Therefore, in the context of the modern world, which remains marked by various forms of authoritarianism and a decline in spiritual values, the messages in Surah Al-Baqarah, verse 258.